2018
DOI: 10.22159/ajpcr.2018.v11i7.25689
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis, Characterization, and Biological Evaluation of Phenylacrylamide Derivatives of Triazoles Derived From Oxazolones

Abstract: Objective: The aim of the present study is to synthesize novel phenylacrylamide derivatives as potent bioactive agents.Methods: Novel N-(3-(4H-1,2,4-triazol-4-ylamino)-3-oxo-1-arylidene prop-2-yl) benzimidic acids (7a-c) have been synthesized by the reaction of 4-(arylidene)-2-phenyloxazol-5(4H)-ones (5a-c) with 4-amino-1, 2, 4-triazole (6) in the presence of anhydrous sodium acetate in glacial acetic acid. Titled compounds (7a-c) were obtained in good yields using microwave technology which resulted in dramat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Some Schiff bases were synthesized in a very short time and excellent yield when the synthesis was conducted under microwave irradiation [7]. The phenyl acrylamide derivatives as potential active agent were also successfully synthesized under microwave irradiation [8]. Energy efficiency in the microwave-assisted solid-state synthesis of cobalt aluminate pigment was also calculated.…”
Section: Introductionmentioning
confidence: 99%
“…Some Schiff bases were synthesized in a very short time and excellent yield when the synthesis was conducted under microwave irradiation [7]. The phenyl acrylamide derivatives as potential active agent were also successfully synthesized under microwave irradiation [8]. Energy efficiency in the microwave-assisted solid-state synthesis of cobalt aluminate pigment was also calculated.…”
Section: Introductionmentioning
confidence: 99%
“…Several advanced techniques such as supercritical fluid extraction, ultrasonic-assisted extraction, and microwave-assisted extraction (MAE) have been used in attempts to improve the efficiency of extraction methods by minimizing the extraction time and solvent usage while maximizing yield. Although all of these methods have their own requirements, a comparative analysis showed that MAE is faster, uses less material, and requires less solvent [7,9,11].…”
Section: Introductionmentioning
confidence: 99%